Respostas

A melhor resposta!
2013-05-09T09:34:02-03:00

Primeira derivada:

 

2y+y'\cdot{e^x}+y\cdot{e^x}+2e^{2x}=0

 

Segunda derivada:

 

2y'+y''\cdot{e^x}+y'\cdot{e^x}+y'\cdot{e^x}+y\cdot{e^x}+4e^{2x}=0

 

Terceira derivada:

 

2y''+y'''\cdot{e^x}+y''\cdot{e^x}+y''\cdot{e^x}+y'\cdot{e^x}+y''\cdot{e^x}+y'\cdot{e^x}+y'\cdot{e^x}+y\cdot{e^x}+8e^{2x}=0

 

Isolando y''' e agrupando termos semelhantes, temos:

 

\boxed{y'''=\frac{-3y'\cdot{e^x}-3y''\cdot{e^x}-y'\cdot{e^x}-2y''-8e^{2x}}{e^x}}

 

Acredito que seja isso, abraços !

1 5 1